Investigation of a cold-based ice apron on a high-mountain permafrost rock wall using ice texture analysis and micro-14C dating: a case study of the Triangle du Tacul ice apron (Mont Blanc massif, France). Issue 266 (10th December 2021) - Guillet, Grégoire; Preunkert, Susanne; Ravanel, Ludovic; Montagnat, Maurine; Friedrich, Ronny
Abstract: The current paper studies the dynamics and age of the Triangle du Tacul (TDT) ice apron, a massive ice volume lying on a steep high-mountain rock wall in the French side of the Mont-Blanc massif at an altitude close to 3640 m a.s.l. Three 60 cm long ice cores were drilled to bedrock (i.e. the rock wall) in 2018 and 2019 at the TDT ice apron. Texture (microstructure and lattice-preferred orientation, LPO) analyses were performed on one core. The two remaining cores were used for radiocarbon dating of the particulate organic carbon fraction (three samples in total). Microstructure and LPO do not substantially vary with along the axis of the ice core. Throughout the core, irregularly shaped grains, associated with strain-induced grain boundary migration and strong single maximum LPO, were observed. Measurements indicate that at the TDT ice deforms under a low strain-rate simple shear regime, with a shear plane parallel to the surface slope of the ice apron. Dynamic recrystallization stands out as the major mechanism for grain growth. Micro-radiocarbon dating indicates that the TDT ice becomes older with depth perpendicular to the ice surface. We observed ice ages older than 600 year BP and at the base of the lowest 30 cm older than 3000 years.